Living with breast cancer, a Lebanese experience - Doumit, Myrna A.A. (2010)
Aim The purpose of this qualitative phenomenological study is to provide in-depth understanding of the experience of Lebanese women living with breast cancer. Background Breast cancer is the most frequently diagnosed cancer in women worldwide. In Lebanon, a country of 4 million people, breast cancer is as well the most widespread type of cancer among Lebanese women. The meaning of cancer diagnosis, the meaning of childbearing and femininity all have cultural bases in Lebanon. The international literature lacks information on how Lebanese women live with breast cancer when compared with women of other cultures. Method The study followed purposeful sampling and saturation principles in which 10 participants with a mean age of 51.3 years were chosen based on their actual knowledge of the phenomenon, and their readiness to share that knowledge. Data were collected between December 2007 and May 2008. All interviews were audio-taped and transcribed verbatim. Data were analyzed based on the Utrecht School of Phenomenology. Findings Four major core themes describing the participants' lived experience emerged from the interviews: Living with losses; living with guilt feeling; living with fears and uncertainty; Living with the need to know and to share that knowledge. Conclusion The experience of Lebanese women with breast cancer revealed distinctive themes not reported by other women from other cultures. The results of this study challenge health care providers and educators to be aware of the difficulties that Lebanese women are facing when they are living with breast cancer.